Hierarchically porous Pd/NiO nanomembranes as cathode catalysts in Li-O2 batteries. (December 2016) - Lu, Xueyi; Yin, Yin; Zhang, Long; Xi, Lixia; Oswald, Steffen; Deng, Junwen; Schmidt, Oliver G.
Abstract: Exploring highly efficient electrocatalysts is crucial for aprotic Li-O2 batteries. Pd/NiO nanomembranes with hierarchical pores are fabricated and employed as cathode catalysts in Li-O2 batteries. By means of standard photolithography, ordered macropores were prepared in the nanomembranes. Moreover, we developed a facile template-free method to create nanopores with sizes ranging from 50 to 200 nm in the composite. The diverse pores of micro- and nanometer sizes and the resulting loose structure supply fast channels for the transportation of reactants, thus efficiently promoting the performance of Li-O2 batteries by lowering the overvoltages and enhancing the rate capability and stability. Highlights: Hierarchically porous Pd/NiO nanomembranes were used as catalysts of Li-O2 batteries. Ordered macropores were prepared in the membranes by means of standard lithography. A facile template-free method was developed to create nanopores in the membranes. The diverse pores and the resulting loose structure contribute to the high performance.